PENGETAHUAN REMAJA TENTANG PENDIDIKAN KEPENDUDUKAN DI DAERAH ISTIMEWA YOGYAKARTA - , Yusuf Prasetyo ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One reason why Indonesian nation to this day still continues to struggle with population problems was caused by lack of public awareness about population problem start from the nation's elite up to family level. Lack of awareness is a result from lack of public knowledge about the condition of Indonesian population at this time, so it is necessary to solve the population problem with a mode that form a mindset, attitudes, and behavior of people who are sensitive and responsive to the population problem. One mode considered as the most effective to establish the pattern and behavior is through population education. This study aims to determine the level of adolescent knowledge about population education and factors that influence adolescent knowledge about population education. The study was conducted on 200 adolescent in 5 districts/cities in Daerah Istimewa Yogyakarta. Data collection is carried out by using a questionnaire and analyzed statistically using the chi-square test and binary logistic regression at Î± = 5 %. The analysis showed that 60 percent of adolescent in Daerah Istimewa Yogyakarta has a low level of knowledge about population education, there are differences level of adolescent knowledge about population education in 5 district/cities in Daerah Istimewa Yogyakarta, and factors that significantly influence the level of adolescent knowledge about population education is the education level (significance 0.002) and access to mass media (significance 0.008).